PENGARUH KEAKTIFAN DAN MINAT TERHADAP HASIL BELAJAR SISWA POKOK BAHASAN TRIGONOMETRI MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH DI KELAS XSMA 15 SEMARANG - Wigati, Sri (Universitas Muhammadiyah Semarang, 2018)
Students enthusiasm and interest in learning mathematics are factors that influence learning outcomes. Where in the application of problem-based learning models on trigonometric material that aims to improve learning outcomes, but in the application process will also appear the activeness of students during the learning process takes place. This is intended to supplement the problem-based learning process in stages, including: understanding the problem, making a solution plan, implementing the plan, and reviewing the results obtained. From these stages there will also appear student activity and interest in the mathematics learning process which certainly contributes to learning outcomes. So the purpose of the study is to determine the effect of activeness and interest in student learning outcomes on trigonometry subjects through problem-based learning models. This research was designed using the One-Shot Case Study design. In this design there is only one group treated. The population in this study were all students of SMA Negeri 15 Semarang. With the sampling technique in this study using the Random sampling technique, obtained a sample of students in class X 7. The variables used are the activeness and interest of students and are learning outcomes. The results of the study concluded that there was a significant influence between activity and interest in learning outcomes with a significant effect of 81.8% in the implementation of problem-based learning models.